Synthesis and characterization of aromatic copolyesters containing siloxane linkages in the polymer backbone - Waghmare, P. B.; Idage, Susheela B.; Menon, Shamal K.; Idage, Bhaskar B. (Journal of Applied Polymer Science, 2006)
A new series of aromatic copolyesters containing siloxane linkages were prepared by the melt polymerization of bisphenol A (BPA) with eugenol end-capped siloxane (EuSi), diphenyl terephthalate (DPT), and diphenyl isoplithalate (DPI) in varying ratio in the temperature range 220-290 degrees C under reduced pressure in the presence of dibutyl tin dilaurate (DBTL) catalyst. The siloxane copolyesters prepared were characterized by FTIR, H-1-NMR spectroscopy, solution viscosity, thermogravimetric analysis, differential scanning calorimetry, and X-ray diffraction. The effect of incorporation of eugenol end-capped siloxane was studied on the properties of BPA/DPI/DPT copolyesters. The glass-transition temperature of copolyester was decreased from 184 to 70 degrees C by incorporation of 20% of eugenol endcapped siloxane. All copolyesters were found to be soluble in commonly used aprotic polar solvents and had film-forming properties. (c) 2006 Wiley Periodicals, Inc.
Keywords: aromatic copolyesters; Bisphenol A; diphenyl isophthalate; diphenyl terephthalate; eugenol end-capped siloxane; melt polymerization

Synthesis and magnetic properties of barium-calcium hexaferrite particles prepared by sol-gel and microemulsion techniques - Jotania, R. B.; Khomane, Ramdas B.; Chauhan, C. C.; Menon, Shamal K.; Kulkarni, B. D. (Journal of Magnetism and Magnetic Materials, 2008)
The preparation of W-type hexaferrite particles with the composition BaCa2Fe16O27 by microemulsion and a stearic acid sol - gel method with and without surfactant has been investigated at various sintering temperatures. The structural and magnetic characteristics have been studied by X-ray diffraction ( XRD), a vibrating sample magnetometer ( VSM), scanning electron microscopy ( SEM), thermogravimetric analysis ( TGA), differential scanning calorimetric ( DSC) and Fourier transform infrared ( FTIR) techniques. The effect of sintering temperature on the properties of BaCa2Fe16O27 hexaferrites has been studied. The value of saturation magnetization ( M-s) depends on types of surfactant used. The sample prepared in the presence of polyoxyethylene ( 20) sorbitan monooleat ( Tween 80) shows low saturation magnetization ( M-s 15.10 emu/g), whereas the other sample prepared in the presence of a surfactant cetyltrimethylammonium bromide (CTAB) exhibits high saturation magnetization (M-s = 24.60 emu/g) compared to the normal sample. (C) 2007 Elsevier B. V. All rights reserved.
Keywords: BaCa2Fe16O27; hexaferrite; magnetic property; Microemulsion; Sol-gel method; surfactant

Sustainable polyacetals from isohexides - Rajput, B. S.; Gaikwad, S. R.; Menon, Shamal K.; Chikkali, Samir H. (Green Chemistry, 2014)
A single step synthetic protocol to access a small family of renewable diacetals was established. The resultant chiral diacetals are valuable building blocks in pharmaceuticals and materials science. To demonstrate their synthetic competence, isohexide-diacetals (2a-c) were subjected to acetal metathesis polymerization and the corresponding polymers (poly2a-c) were isolated as white solids with molecular weights in the range 3200-27 600 (g mol(-1)). The semi-crystalline polymers displayed glass transition temperatures between 38-65 degrees C and melting temperatures in the range 103-156 degrees C. The isohexide derived polyacetats are stable under practical washing and rinsing conditions but degrade in slightly acidic media.

Synthesis of renewable copolyacetals with tunable degradation - Rajput, Bhausaheb S.; Chander, Umesh; Arole, Kailash; Stempfle, Florian; Menon, Shamal K.; Mecking, Stefan; Chikkali, Samir H. (Macromolecular Chemistry and Physics, 2016)
Acetal metathesis copolymerization (AMCP) of renewable isohexide diacetals and aliphatic long-chain diacetals is reported and access to a small family of copolyacetals has been established. Crucial 1-2D NMR and MALDI-ToF-MS findings unambiguously confirm the existence of a copolymeric structure. In a stark contrast to the earlier reported isohexide-polyacetals, the current copolyacetals reveal very slow degradation. Hydrolytic degradation of copolyacetal pellets is extremely slow at pH 7, whereas only 30% degradation over a period of 15 d is observed in 9 M hydrochloric acid solution. GPC investigations reveal that with increasing chain-length the rate of degradation reduces, whereas copolyacetals with short-chain aliphatic segments display a faster degradation profile. The reduced rate of degradation can be attributed to the hydrophobic nature of long-chain acetal segments. In situ NMR spectroscopy reveals the existence of formates, hemiacetals, and diols as degradation products. Thus, the rate of degradation can be tuned by the judicious choice of isohexide-diacetal and linear-diacetals in a copolyacetal.
Keywords: copolyacetals; degradable polymers; diacetals; isohexides; renewable polymers

Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers